Creation of cucumber lines with a high degree of parthenocarpy - I. B. Korottseva; S. N. Belov (Овощи России, 2025)
Relevance. In protected ground cucumber is one of the most profitable crops due to its high rate of maturity, shade tolerance, yield and possibility to get fresh fruits almost all year round. Vegetable producers prefer parthenocarpic hybrids of cucumber, as small-fruited lumpy cucumber hybrids of parthenocarpic type for universal use are in great demand among consumers. The advantages of parthenocarpic hybrids compared to bee-pollinated hybrids are higher early yield, ability to set fruit without pollination in any weather. Unfortunately, the main areas in the protected ground are occupied by foreign hybrids of parthenocarpic type, so the selection of domestic competitive parthenocarpic hybrids of cucumber for spring film greenhouses is currently quite relevant.Materials and Methods. The experiment was laid in 2021-2023 in Odintsovsky district of Moscow region in the conditions of the ground spring film greenhouse of the type ‘Block’ on the basis of the head institution of FSBSI FSVC. To study parthenocarpy, the aligned selection material obtained earlier as a result of selections and four or more insuchtings (self-pollinations) was involved in the work. During 3 years, about 40 breeding lines of cucumber were evaluated annually for this trait. In 2023 we studied the inheritance of parthenocarpy trait by F1 hybrids on 27 hybrid combinations from crosses of 13 maternal and 15 paternal forms, evaluating the hp indicator ‘degree of dominance’.Results. Rigid selection of cucumber breeding samples on the degree of parthenocarpy, during 3 years, allowed to improve this trait on average by 10.3-17.1%, depending on the year of research and genotypes of the studied samples. We selected 3 lines (L-132, L-135, L-161) of female flowering type, which differ not only by high degree of parthenocarpy, but also by stability of this trait manifestation over the years. The manifestation of parthenocarpy in F1 hybrids largely depended on the genotype of the initial forms used in hybridisation and varied from positive heterosis to negative dominance and even negative heterosis. In our experience, 45% of hybrid combinations showed positive heterosis effect on this trait, indicating the possibility of creating hybrid combinations with a higher level of parthenocarpy compared to the parental forms. Hybrid combinations with the highest heterosis effect on the parthenocarpy degree, compared to the parental forms, were identified. One of these combinations, according to the results of 2-year evaluation of the complex of economically useful traits transferred for testing to the State Commission of the Russian Federation for testing and protection of breeding achievements (FGBU GOSSORTKOMISSIA"), according to expert evaluation, in 2023 under the name F1 Dendi.